ANALISIS PENETAPAN STRATEGI PENINGKATAN TINGKAT KOMPONEN DALAM NEGERI (TKDN) PADA INDUSTRI MANUFAKTUR DI INDONESIA: STUDI KASUS PADA KOMPONEN KOPLING - Hartono, Gunawarman; Santoso, Edi (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
The development of the manufacturing industry in a country indicates the development of the national industry. The development can be evaluated by both product quality and performance of the industry as a whole. In enhancing the competitiveness of local products, the government attempted to improve the industrys ability to produce a quality product or component. This research was conducted to determine how domestic manufacturing companies have increased their use of domestic components in producing their products. Results of the determination of the value of the domestic component level (DCL) showed that the company manufacturing clutch uses a lot of local components in the country. This is possible because when setting the value of DCL, the human resources involved in the production provided very much contribution.